AFTERCOVID: TOWARDS PRODUCING A WEB-BASED APPLICATION FOR MONITORING LONG COVID SYNDROME PATIENT (Journal of Creative Industry and Sustainable Culture, 2022)
The long-term consequences of COVID-19 or Long COVID syndrome is a normal illness, both physical and emotional affected the ex-COVID-19 patients. Some people with this syndrome still not getting a proper treatment and support, especially mentally support. Thus, AfterCOVID web application been built as a platform to help Long COVID Syndrome patient in their recovery process. This web-based application is developed based on Waterfall model to make sure that process can be synchronized with all the requirements and can be completed in time. Based on this model, there are five phases as guideline, which are Requirement, Design, Implementation, Verification and Maintenance. In general, this AfterCOVID web application allows user to view how many people register to the application so that they know that they are not alone. User also can record their daily health condition such as blood pressure, oxygen saturation and new symptoms. Besides, they can view useful information such as exercises, breathing techniques andany programs that runs by an organization for Long COVID patients. Usability testing has been held for this first AfterCOVID prototype system and it managed to get grade B (78%) from the test result, which is based on System Usability Scale (SUS). Hopefully, this application can help Long COVID Syndrome patients stay stronger and give community knowledge about the effects of COVID-19.